Tales of the quantum : understanding physics' most fundamental theory - Hobson, Art, 1934- (New York, NY : Oxford University Press, 2017)
''Tales of the Quantum' is a discussion of the fundamental principles of quantum physics for the non-scientific reader. Hobson brings together examples that illustrate the simple and logical consistency of what otherwise is viewed as a largely unapproachable topic for anyone but physicists. The book condenses topics like force, motion, and electromagnetism'--
Includes bibliographical references and index.
Keywords: Quantum theory